Isolated insular stroke: topography is the answer with respect to outcome and cardiac involvement - Kuris, Fedra; Tartaglia, Sara; Sperotto, Roberto; Ceccarelli, Laura; Bagatto, Daniele; Lorenzut, Simone; Merlino, Giovanni; Janes, Francesco; Gentile, Carolina; Marinig, Roberto; Verriello, Lorenzo; Valente, Mariarosaria; et al. (Frontiers in Neurology, 2024)
Background and purpose Isolated insular strokes (IIS) are a rare occurrence due to the frequent concomitant involvement of adjacent territories, supplied by the M2 segment of the middle cerebral artery (MCA), and clinical aspects are sometimes contradictory. We aimed to describe clinical and radiological characteristics of a pure IIS case series, focusing on its functional outcome and cardiac involvement. Methods We identified 15 isolated insular ischemic strokes from a pool of 563 ischemic strokes occurred between January 2020 and December 2021. Data collection consisted of demographic and baseline clinical characteristics, comorbidities, electrocardiograms, echocardiograms, stroke topography and etiology, reperfusive treatments, and outcome measures. Descriptive statistical analysis was carried out. Results Newly detected cardiovascular alterations were the prevalent atypical presentation. Cardioembolism was the most frequent etiology. Most of patients had major neurological improvement at discharge and good outcome at 3-months follow-up. Discussion and conclusion IIS are extremely rare, representing according to our study about 2.6% ischemic strokes cases per year, and patients have peculiar clinical manifestations, such as dysautonomia and awareness deficits. Our data suggest the possibility for these patients to completely recover after acute ischemic stroke notwithstanding the pivotal role of the insula in cerebral connections and the frequent association with MCA occlusion. Moreover, given the central role of the insula in regulating autonomic functions, newly detected cardiac arrhythmias must be taken into consideration, as well as a full diagnostic work-up for the research of cardioembolic sources. To our knowledge, this is the largest monocentric case series of IIS and it might be useful for future systematic reviews.